Avaliação clínica dos procedimentos de expansão cirurgicamente assistida da maxila (ECAM) - Ribeiro Jr., Paulo Domingos [UNESP]; Gonçales, Eduardo Sanches; Souza, Paulo César Ulson De; Nary Filho, Hugo [UNESP]; Luz, João Gualberto Cerqueira (Dental Press Editora, 2006)
AIM: clinical evaluation of surgically assisted maxillary expansion. METHODS: the present study evaluated 10 patients who underwent surgically assisted maxillary expansion. The efficacy of the surgical procedure helping transverse maxillary expansion given by the Hyrax, expansion stability, post-operatory discomfort during the activation of the device, the quantity and quality of the expansion achieved, the age of the patients, nasal base alteration, and nasal breathing were analyzed. RESULTS AND CONCLUSIONS: from the results, it was possible to observe that surgically assisted maxillary expansion is an efficient and stable treatment, which offers functional changes and minimal aesthetic alterations.

OBJETIVO: avaliação clínica dos procedimentos de expansão cirurgicamente assistida da maxila. METODOLOGIA: foram avaliados 10 pacientes tratados através da expansão ortopédica com auxílio cirúrgico, conhecida como expansão cirurgicamente assistida da maxila (ECAM). Avaliou-se a efetividade deste procedimento cirúrgico no auxílio à expansão transversal da maxila proporcionada através de aparelho do tipo Hyrax, a estabilidade desta expansão, as ocorrências pós-operatórias, a quantidade e qualidade da expansão conseguida e alterações estéticas deste procedimento. RESULTADOS E CONCLUSÕES: concluiu-se, com um acompanhamento a longo prazo, que a ECAM trata-se de um procedimento eficiente, estável, que proporciona mudanças funcionais e pouca alteração estética facial.
Clinical evaluation of surgically assisted maxillary expansion (SAME)
Keywords: Maxillary expansion; Surgically assisted maxillary expansion; Transverse maxillary deficiency; Expansão cirurgicamente assistida da maxila; Expansão maxilar; Deficiência transversal da maxila